Explaining the spillover from interparental conflict to adolescent adjustment through self-determination theory - Koçak, A.; Mouratidis, A.; Uçanok, Z.; Davies, P.T. (Journal of Child and Family Studies, 2023)
Although the association between interparental conflict and adolescent adjustment is well documented, the intervening mechanisms that explain this relationship are not fully understood. Guided by the spillover hypothesis and the self-determination theory, this study examined whether the associations among interparental conflict and adolescent depressive feelings and life satisfaction were explained by maternal autonomy support and, in turn, by adolescent need frustration. Participants were 925 Turkish adolescents (Mage = 16.08 years, SD = 0.31) and their mothers (Mage = 41.43, SD = 5.16). Results from path analysis showed that interparental conflict was related to lower maternal autonomy support, and in turn to higher adolescent need frustration. Greater need frustration, in turn, predicted higher adolescent depressive feelings and lower life satisfaction six months later. These findings suggested that conflictual parental relationships may predict adolescent adjustment through poor parenting and adolescent need frustration. The findings and related directions for future research are discussed in the context of self-determination theory and its role in advancing a process-oriented understanding of the familial and individual determinants of adolescent adjustment. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.